Analisis Risiko Bahaya Pada Kegiatan Bongkar Muat Batu Bara di PT. Delta Artha Bahari Nusantara - Very Andriyansyah; Merry Sunaryo; Ratna Ayu Ratriwardhani; Muslikha Nourma Rhomadhoni (Peneliti.net, 2022)
Risk analysis of occupational accidents is a work activity in a company so that an effort is needed to analyze hazards and risks by using one of the existing methods, namely HIRARC to minimize the level of accident risk. The purpose of this study is to analyze the risk of hazards in coal loading and unloading activities at PT Delta Artha Bahari Nusanatara using the HIRARC method. The type of research used is descriptive research with observational methods where the techniques used in data collection are natural settings (natural conditions), primary data sources, discussions with K3L and the Head of Operations at the company and data collection techniques are mostly on observations during activities and activities. documentation. Based on the results of the study, at the time of hazard identification, 7 activities and 22 work processes contained 11 different potential hazards including falling into the sea, exposure to hot sunlight, exposure to and inhalation of coal dust, being pinched by mooring ropes, being crushed by loading and unloading equipment, being scratched by loading and unloading equipment. , hit by a dump truck vehicle, crushed by loading and unloading equipment, hit by a rampdoor tool, crushed by a sesek/bamboo board tool, flammable and combustible fuel. Then carry out a risk assessment, namely the results show that of the 11 potential hazards there are 5 low risk, 4 moderate risk, 1 high risk and 1 very high risk, therefore it is necessary to make recommendations for the control needed to reduce the level of risk to a lower level in order to minimize work accidents for reduce the risk of work accidents. Suggestions from company researchers must implement control recommendations, namely the addition of sophisticated trucks cleaning the dock area, Personal Protective Equipment (safety helmets, masks, vests, catelpaks, gloves, sunglasses, and safety shoes), Administrative Approach (Fit to work, MSDS Pertamina dex (Hydrocarbons and Additives) promotion of Occupational Safety and Health (K3)), and Engineering Control (pedestrian paths or pedestrian areas, refueling in a safe place, preparing for disasters (Emergency response plan))